THE LINGUISTIC LANDSCAPE OF KEMANG: A MULTIMODAL ANALYSIS OF BUSINESS NAMING - RAMBE, NUR FITHRI QOMARIAH; Permana, Sudarya (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates strategies of language representation in the business landscape of South Jakarta as a response to the ongoing crisis of local naming. Employing a qualitative descriptive design complemented by multimodal critical discourse analysis, the research analyzes 58 shop names with Kress & van Leeuwen’s representational, interpersonal, and compositional metafunctions, integrated with Harrison’s social semiotic framework. Findings reveal a predominance of conceptual-symbolic processes (55.2%), alongside narrative actional (34.5%) and reactional (10.3%) processes, and interactional strategies emphasizing offer-based naming that construct identity and invite consumer interpretation that negotiate individual and communal identity and hybrid modern-local positioning. The compositional analysis, through Given/New, salience, and framing, underscores how naming constructs visual persuasion and aspirational modernity. The analysis also highlights the use of symbolic capital in visual naming strategies, reflecting businesses’ attempts to assert socio-cultural legitimacy. These findings offer implications for language policy in guiding public spatial planning that emphasizes the role of Indonesian as a marker of national identity. This includes suggestions such as incorporating Indonesian subtitles beneath foreign-language signage without limiting creative expression.